Experimental and Numerical Evaluation of Dynamic Characteristics of 3DOF Reduced-Scale Model - Abderaouf Daci; Nassima Benmansour; Abdellatif Bentifour; Rachid Derbal (The Journal of Engineering and Exact Sciences)
The dynamic behavior of structures subjected to seismic excitations is often predicted by numerical models based on the finite elements method. The reliability of the results of the numerical models must be subject to experimental validation. To achieve this, experimental tests using shaking tables lead to a more realistic prediction of the dynamic behavior of civil engineering structures. The main objective of this work is to develop an experimental procedure to determine the dynamic characteristics of civil engineering structures under seismic excitations. These dynamic characteristics are vital for understanding the real dynamic behavior of structures. For this, a three-degree-of-freedom (3DOF) reduced model of a steel structure adopting a 1:6 scale is developed. It is composed of three-level steel frames. Experimental tests are conducted using the shaking table of the RISAM laboratory (Risk Assessment and Management) at the University of Tlemcen. This work is focused on the two main dynamic characteristics of the reduced model, namely the predominant frequencies and the damping. The predominant frequencies of this reduced model are determined using a frequency sweep under a low-intensity white noise signal. This experimental procedure aims to detect the predominant frequencies by converting the recorded time history response to a signal depending on frequencies. Based on the logarithmic decrement method, the damping ratio is calculated. Next, a three-dimensional finite elements model of the reduced model is established. Several dynamic analyses of the finite elements model are performed. The experimental and numerical results are compared and discussed. The results obtained through these experimental tests show that the procedure used to determine the dynamic characteristics of this reduced model is very effective. Moreover, a perfect similarity is found between the experimental and numerical results.